On-road Vehicle Emission Inventory and Its Characteristics Analysis in Northeast China: A Case Study of Changchun, China - Gao, Chengkang; Ba, Qiao; Song, Kaihui; Xu, Qingjiang; Xing, Yuhong; Chen, Weiwei; Yu, Zhenbo; Na, Hongming; Wang, Sen (Journal of Environmental Accounting and Management, 2026)
The transportation sector in Northeast China is facing challenges of fuel combustion and vehicle maintenance, like many high latitude areas, for the cold weather, long-lasting snow and associated slippery roads. The high reliance on vehicles rather than bicycles reinforced the challenges, resulting in inefficient fuel burning and high emissions from mobility. To better understand transportation emissions from cold areas and inform emission control strategies, this study analyzed the temporal and spatial dynamics of transport emissions in 2016, taking Changchun city as a typical city representing northeast China. Based on field investigation and national motor emission guideline, this study established a 1km×1km spatial highresolution emission inventory for atmospheric pollutants in Changchun City and analyzed emission responsibility from different types of vehicles. The results showed that the annual emissions of atmospheric pollutants CO, HC, NOx, PM2.5, and PM10 from road movement sources in 2016 in Changchun were 137,700 tons, 29,000 tons, 40,900 tons, 2200 tons and 2400 tons, respectively. Small passenger vehicles had the highest contribution rates to CO and HC emissions, which were 47.8% and 57.9% respectively. Heavy trucks had the highest contribution rates to NOx and PM which were 41.5% and 43.85%, respectively. Small passenger cars and heavy-duty trucks are the focus of future road source air pollution control. On the spatial level, the emission intensity of atmospheric pollutants from road movement sources in Changchun showed a trend of decreasing from city center to urban edge, especially concentrated in the square areas enclosed by the eastern urban expressway, southern urban expressway, western urban expressway and northern urban expressway.